1896
DOI: 10.5479/si.00963801.1108.255
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the Hemiptera of Japan, presented to the United States National Museum by Professor Mitzukuri

Abstract: It embraces the greatest number of si^ecies of this order which have thus far been made accessible for scientific study. The museums of Europe are not rich in collections of these insects from Japan, and it is only within the last twenty-five years that much attention has been given to their acquisition. Thunberg was the first to describe any considerable number of the species, and a lapse of thirtj^-five years took place before Motschulsky next took up the subject and described a few additional species. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Notes. H. sellatus was originally described by Uhler [58] as Thammotettix sellata from Japan based on two female specimens that are deposited in the U.S. National Museum. Unfortunately, Thamnotettix sellata Uhler was confused with Acocephalus discigutta Walker for a long time because of the absence of information on the male genitalia.…”
Section: Resultsmentioning
confidence: 99%
“…Notes. H. sellatus was originally described by Uhler [58] as Thammotettix sellata from Japan based on two female specimens that are deposited in the U.S. National Museum. Unfortunately, Thamnotettix sellata Uhler was confused with Acocephalus discigutta Walker for a long time because of the absence of information on the male genitalia.…”
Section: Resultsmentioning
confidence: 99%
“…Diostrombus politus Uhler, : p. 284; Matsumura : p. 210; Muir : p. 49; Metcalf : pp. 29–30; Nast : p. 77; Lee and Kwon : p. 94; Morimoto : p. 87; Kwon and Huh : p. 41, Kwon and Huh : pp.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study (Watanabe et al, 2014) illustrated extensive intranuclear Rickettsia infections of sperm of a leafhopper (Nephotettix cincticeps (Uhler, 1896)). The authors furthermore demonstrated for the first time that these endosymbionts are efficiently transmitted paternally via an intrasperm passage, without depressing sperm function.…”
Section: Evolutionary and Functional Implicationsmentioning
confidence: 98%